Medio ambiente y desarrollo: ¿un puente demasiado lejos? - Solano, David (1995)
It tries to provide a global vision of how the environmental issue is being handled by the government and businessmen of Peru, as well as to warn about the consequences that the current trend can bring for the development of the country. It maintains that, although the Environmental Code was promulgated, its scope was moderated shortly afterwards through other legal instruments aimed at promoting investment. In the same way, it is affirmed that the creation of a rector, the National Environment Council, will not be a guarantee for the solution of environmental problems either. On the other hand, the very little importance that Peruvian managers give to the preservation of the environment in comparison with those of other countries stands out. Finally, it is affirmed that in order to care the natural heritage, it is necessary to become aware of the complementarity between development and the environment, and that, in the face of this situation, the State is obliged to promote clean technologies that ensure the exploitation of the country's assets and, at the same time, help to preserve them, so that future generations can take advantage of them.